The Play of International Practice - Bueger, Christian; Gadinger, Frank (International studies quarterly, 2015)
The core claims of the practice turn in International Relations (IR) remain ambiguous. What promises does international practice theory hold for the field? How does the kind of theorizing it produces differ from existing perspectives? What kind of research agenda does it produce? This article addresses these questions. Drawing on the work of Andreas Reckwitz, we show that practice approaches entail a distinctive view on the drivers of social relations. Practice theories argue against individualistic-interest and norm-based actor models. They situate knowledge in practice rather than “mental frames” or “discourse.” Practice approaches focus on how groups perform their practical activities in world politics to renew and reproduce social order. They therefore overcome familiar dualisms—agents and structures, subjects and objects, and ideational and material—that plague IR theory. Practice theories are a heterogeneous family, but, as we argue, share a range of core commitments. Realizing the promise of the practice turn requires considering the full spectrum of its approaches. However, the field primarily draws on trajectories in international practice theory that emphasize reproduction and hierarchies. It should pay greater attention to practice approaches rooted in pragmatism and that emphasize contingency and change. We conclude with an outline of core challenges that the future agenda of international practice theory must tackle.